ANALYSIS OF ENVIRONMENTAL ACCOUNTING ACTUALIZATION ON ENVIRONMENTAL COSTS AS AN EFFORT FOR SOCIAL RESPONSIBILITY AT PT. PN XIV SOUTH SULAWESI - Andi Nurrahma Gaffar; Muhammad Ikram. S; Indra Kusumawati; Muh. Abdi Imam (JURNAL ILMIAH EDUNOMIKA, 2024)
The objective of this study is to examine the Company's Environmental Accounting Actualization by identifying, acknowledging, quantifying, presenting, and reporting environmental expenses in financial statements. The study was carried out at PT. PN XIV South Sulawesi. This study employs primary qualitative data via interviews and secondary quantitative data derived from firm financial records. The findings indicate that corporations acknowledge the operational expenses associated with trash management (environmental costs) as a part of their production costs, taking into account that waste is generated as a by-product of the manufacturing process. Currently, there are no explicit regulations in accounting standards for the disclosure of environmental concerns in financial reports. Therefore, each firm has the freedom to apply its own policy in this regard.